Changes in Stroke Volume After Renal Denervation: Insight From Cardiac Magnetic Resonance Imaging. Issue 3 (March 2020) - Lurz, Philip; Kresoja, Karl-Patrik; Rommel, Karl-Philipp; von Roeder, Maximilian; Besler, Christian; Lücke, Christian; Gutberlet, Matthias; Schmieder, Roland E.; Mahfoud, Felix; Thiele, Holger; Desch, Steffen; Fengler, Karl
Abstract : Recent trial results support catheter-based renal denervation (RDN) for treatment of hypertension, while the exact mechanisms causing blood pressure to fall remain incompletely understood. Cardiac magnetic resonance imaging was used to assess the effects of RDN on cardiac function in patients with hypertension undergoing RDN and compared with sham treatment. Cardiac magnetic resonance imaging was used to assess stroke volume index, cardiac index, heart rate, systemic vascular resistance index, and stroke work index from aortic flow measurements. Patients with resistant hypertension from a randomized, sham-controlled RDN trial underwent cardiac magnetic resonance imaging before RDN and at follow-up (randomized cohort). Results were then validated in a cohort of patients with resistant hypertension undergoing RDN and cardiac magnetic resonance imaging (validation cohort). In total, 162 patients were included 52 patients in the randomized trial (27 shams) and 110 patients in the validation cohort. In the randomized cohort, stroke volume index was reduced by 4.7±9.8 mL/m 2 in the RDN cohort and remained unchanged in the sham cohort ( P =0.008 for between-group comparison), while cardiac index and stroke work index tended to be reduced in RDN patients but not in sham patients (−0.10±5.9 versus 0.17±0.51 L/min per m 2 and −7.1±12.5 versus −1.4±10.4 g/m 2, P =0.08 for both). In contrast, systemic vascular resistance index and heart rate remained unchanged after RDN. In the validation cohort, reduction of stroke volume index was confirmed, and cardiac index and stroke work index were also reduced significantly, whereas systemic vascular resistance index and heart rate remained unchanged at follow-up. In this study of patients with resistant hypertension, RDN resulted in a reduction of stroke volume when compared with sham.